Institutional and organisation analysis of BRAC Education Programme (in the framework of BEP phase IV, 2004-2009): August 24 - September 13, 2003 - Gerwen, Frans Van; Prakke, Diederik; Rakels, Han (© BRAC, 2016)
1. Approach and methodology 2. Learning from earlier mission 3. Institutional and organisation description and analysis of BEP 4. Conclusion and Recommendations.